His private secretary - Whitman, Phil; Wayne, John, 1907-1979; Knapp, Evalyn, 1908-1981; Colam Pictures Co.; Screencraft Productions; Cinetel Films ([Los Angeles, CA] : Screencraft Productions, 1933)
"Dick Wallace wants to marry a minister's grand-daughter but his father, who wants him to get work on his company's business, is opposed. She takes a job with the company to prove she's okay." --
Evalyn Knapp, John Wayne, Reginald Barlow, Alec B. Francis, Arthur Hoyt, Natalie Kingston, Patrick Cunning, Al St. John, Hugh Kidder, Mickey Rentschler.
Photography, Abe Scholtz; editor, Robert Ray.
MPAA rating: G.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 8, 2015)
Keywords: Secretaries -- Drama; Man-woman relationships -- Drama; Fathers and sons -- Drama; Collection agencies -- Drama; Comedy films; Feature films; Fiction films; Internet videos; Streaming video